(untitled) (Journal of Informatics Education and Research, 2025)
This paper analyses the long run as well as short term relationship between GDP Growth Rate, Trade Openness and Real Exchange Rate with respect to Indian Economy. By using Auto Regressive Distributor Lag (ARDL) Model, the unrestricted and restricted Error Correction Model (ECM) are established. It finds a cointegrated long run association among these three variables. Choosing the correct lag (AIC -4.33, SIC-4.83) and applying it in Lagrange Multiplier (LM) test, this model verifies that errors are uncorrelated. Stability and Fitness of the model is also judged by Cumulative Sum Control (CUSUM) Test. Further, in the context of measuring the short-term relationship, the Error Correction Term signifies that there are 100% chances of rectification of disequilibrium in the next period to reach its equilibrium. Overall, the study shows that the impact of Trade Openness and Real Exchange Rate on GDP Growth Rate is positive (0.1581) and negative (-0.5122) respectively.